2017
DOI: 10.1038/ncomms15207
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of IDO-kynurenine-AhR metabolic circuitry abrogates IFN-γ-induced immunologic dormancy of tumor-repopulating cells

Abstract: Interactions with the immune system may lead tumorigenic cells into dormancy. However, the underlying molecular mechanism is poorly understood. Using a 3D fibrin gel model, we show that IFN-γ induces tumour-repopulating cells (TRCs) to enter dormancy through an indolamine 2,3-dioxygenase 1 (IDO1)-kynurenine (Kyn)-aryl hydrocarbon receptor (AhR)-p27 dependent pathway. Mechanistically, IFN-γ signalling triggers differentiated tumour cell apoptosis via STAT1; however, when IDO1 and AhR are highly expressed as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 68 publications
6
159
3
Order By: Relevance
“…In contrast, less than 8% of CD133 -B16 cells could grow into colonies in the soft 3D fibrin gels, consistent with our previous report (30), suggesting that CD133 hi melanoma cells represent TRCs. Thus, in the following studies, we used in vitro culture-enriched and expanded melanoma TRCs to investigate the mechanistic aspects of how IFN-β induces stem-like melanoma cells into dormancy.…”
Section: Ifn-β Induces Melanoma Trcs Into Dormancy In Vitrosupporting
confidence: 75%
See 2 more Smart Citations
“…In contrast, less than 8% of CD133 -B16 cells could grow into colonies in the soft 3D fibrin gels, consistent with our previous report (30), suggesting that CD133 hi melanoma cells represent TRCs. Thus, in the following studies, we used in vitro culture-enriched and expanded melanoma TRCs to investigate the mechanistic aspects of how IFN-β induces stem-like melanoma cells into dormancy.…”
Section: Ifn-β Induces Melanoma Trcs Into Dormancy In Vitrosupporting
confidence: 75%
“…For conventional 2D cell culture, tumor cells were maintained in a rigid dish with complete culture medium. TRC culture was performed according to our previously published protocol (13,15,30) with some modification. In brief, fibrinogen (Searun Holdings Co.) was dissolved at -4°C overnight and, once completely dissolved, was diluted into 2 mg/ml with T7 buffer (pH 7.4, 50 mM Tris, 150 mM NaCl).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that IFNγ signaling elicits apoptosis of differentiated tumor cells via STAT1. However, Liu and colleagues showed that IFNγ signaling resulted in IDO1/AhR‐dependent p27 induction when IDO1 and AhR were highly expressed in tumor‐repopulating cells (TRCs) . The p27 in turn bound to cytosolic pSTAT1, which prevented STAT1‐mediated tumor cell apoptosis.…”
Section: The Role Of Ifnγ In Tumor Escapementioning
confidence: 99%
“…IFN- γ mediated tumor dormancy can also be induced independent from STAT1 signaling. Tumor clones that highly express indolamine 2,3-dioxygenase 1 (IDO1) and kynurenine (Kyn)-aryl hydrocarbon receptor (AhR) respond to IFN- γ by upregulating the cell cycle inhibitor p27, consequently preventing STAT1 signaling and inducing tumor dormancy [25]. In fact, p21 and p27 facilitate hypo-phosphorylation of the tumor suppressor Rb, thereby suppressing the activity of E2F transcription factor and inhibiting the activation of genes involved in cell proliferation.…”
Section: Introductionmentioning
confidence: 99%